Study of Collocation Occurrence in English Essay Writing: The Case Study of Three Northern University - Chaimongkol, Thisakon (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2020)
The purposes of this study aimed to investigate the types of collocation used by Thai students in three northern universities, and to examine the types of collocation from the Thai learners comparing with native English. The criteria were used with 2 corpora. The data of this study were gathered from 213 essays written by Thai learners in three northern universities. The collocation found were analyzed and compared with the Oxford Collocations Dictionary for students of English (Second Edition) (2009) and COCA (Corpus of Contemporary American English). The findings revealed that there were 1,858 collocations used by the participants. The most frequent collocation pattern was Adjective + Noun collocation (1,085 instances; 58.40%), followed by Verb + Preposition collocation (432 instances; 23.25%), Verb + Noun collocation (201 instances; 10.82%), and Noun + Noun collocation (140 instances; 7.53%), Moreover, the ability for using collocation words was found in the Oxford Collocation Dictionary and COCA Corpus which were used to analyze by percentage. In conclusion, the frequency of collocation used revealed the use of Verb+Preposition, Adjective+Noun, Verb+Noun, and Noun+Noun, respectively.